A Bacterial Toxin that Causes DNA Damage to Modulate Cellular Responses. (2001) - Lara-Tejero Lara-Tejero, Maria Maria
Abstract : Campylobacter jejuni constitutes the leading cause of bacterial diarrhea in the U.S. and all around the world [1]. This common bacterium produces a toxin known as cytolethal distending toxin (CDT) [2] which causes intoxicated cells to enlarge and to stop dividing with a double DNA content characteristic of G2/M arrest [3]. The effect of the toxin on the cell is so striking that it captivated scientists for a long time. However, its mechanism of action had remained elusive.